Match-related technical performance of qualified and eliminated teams in the group stage of Qatar 2022 World Cup - Kahlouche, I. Z. (Trends in Sport Sciences, 2023)
Introduction. Match-related technical performance is one of the most important factors for success in modern soccer. Aim of Study. This study aimed to try to determine which of the attacking and goal scoring, passing and organizing and defending variables contributed to the success of the national teams participating in the Qatar 2022 FIFA World Cup to qualify for the knockout stage. Material and Methods. The sample consisted of 48 group stage matches. The data were collected from the Whoscord website, which is based on the OPTA system. Results. Results showed that there are statistically significant differences between qualified and eliminated teams in goal efficiency and pass accuracy (p < 0.05). However, the effect size was moderate in variables of goal efficiency (ES = 0.74), pass accuracy (ES = = 0.78), total passes (ES = 0.69), and short passes (ES = 0.62). Other variables have small or trivial effect. Conclusions. In conclusion, goal efficiency, pass accuracy are the important success factors in stage group of 2022 World Cup. Therefore, coaches must focus heavily on these variables in their training in order to succeed in qualifying for the knockout stage in the upcoming World Cup tournaments.